A numerical study of flutter in a transonic fan - Isomura, K; Giles, M (ASME, 1998)
The bending mode flutter of a modern rr transonic fan has been studied using a quasi-three-dimensional viscous unsteady CFD code. The type of flutter in this research is that of a highly loaded blade with a tip relative Mach number just above unity, commonly refer red to as transonic stall flutter. This type of flutter is often encountered bz modern wide chord fans without a part span shr-oud. The CFD simulation uses an upwinding scheme with Roe's third-order flux differencing, and Johnson and King's turbulence model with the later modification due to Johnson and Coakley. A dynamic transition point model is developed using the e(n) method and Schubauer and Klebanoff's experimental data. The calculations of the flow in this fan reveal that the source of the flutter of IHI transonic fan is an oscillation of the passage shock, rather than a stall. As the blade loading increases, the passage shock moves forward. Just before the passage shock unstarts, the stability of the passage shock decreases, and a small blade vibration causes the shock to oscillate with a large amplitude between unstarted and started positions. The dominant component of the blade excitation force is due to the foot of the oscillating passage shock on the blade pressure surface.